Pengembangan LKPD Berbasis Inquiry Learning Berbantuan Media Simulasi dengan Modellus pada Materi Gerak Melingkar Beraturan - Susilawati Susilawati; Ishafit Ishafit (Universitas Muhammadiyah Purworejo, 2020)
This study aims to develop LKPD using simulation media with Modellus in circular motion irregular. The experimental subjects in this study are students of SMK class X. The model used is the ADDIE development model which includes 5 stages: Analysis, Design, Development, Implementation, and Evaluation. To know the feasibility of media validation. This validation is in the form of a questionnaire with predetermined criteria and indicators. The development of LKPD conducted test of material experts, media experts, and users with a percentage of 79.68%, 77.27%, and 77.00%. With that percentage, the worksheets of students using simulated media aid with Modellus are categorized as viable media